How E-Security and E-Trust impact on E-Service quality in Online Shopping : A case of eBay United Kingdom - Senadzo, Patrick Kwablah (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
This research sought to explore the extent e-security and e-trust impact service quality on online buying among customers using a case of eBay e-retailing platform. This was necessitated by the worrying increase in online fraud coupled with personal data getting into wrong hands. Such developments have created anxiety among online shoppers negating the gains that could be made in adopting online facilities as marketing tool. The research was based on interpretive stance of the philosophical knowledge of inquiry adopting subjective approaches to gather data through group discussion and in-depth interview where a total sample of four(4) for the in-depth interview and six(6) for the focus group discussions. The frame was people between the age group of 20-35 living within Cardiff and have made purchases from eBay within a two month period. . This research found insights which were far reaching, confirming that of e-service quality is dependent on e-security and e-trust, without which satisfaction will be void. The research also identified other e-service quality pre-requisite variables including; item origination, delivery of item, reviews on product and seller, return policy, item description, types of e-security and e-trust.